(untitled) (Research, Society and Development, 2024)
This production tries to highlight the special education that has been gaining space in regular schools. However, it cannot be said that this walk was a carpet of flowers in view of finding thorns, which have been trimmed until today, amid the perceptions of the different horizons of teaching challenges to work on learning with students in the Specialized Educational Service - AEE room. Objective: to present the results of the teaching work in special rooms of the Professora Zélia Flexa da Silva School, in the municipality of Magalhães Barata, in the state of Pará. Methodology: field research, social (done with people), of a quantitative-qualitative nature, with a descriptive approach carried out at the Professora Zélia Flexa da Silva School, in the municipality of Magalhães Barata/Pa. Results: the sample consisted of the participation of 10 (ten) teachers who work with special students at the Professora Zélia Flexa da Silva School, in the municipality of Magalhães Barata/PA. Final Considerations: It was found that the challenges of teachers in the Specialized Educational Service room begin with the fear of this teacher, not feeling competent with the attributions imposed on him, as well as identifying in the common rooms this student who needs to be assisted, making relational contact with the family and organizing the entire apparatus of pedagogical resources, using strategies that ensure the accessibility of this student considering the individuality, potentiality and ability for this student to advance and succeed in his educational path.